A mycotic abdominal aortic aneurysm caused by Listeria monocytogenes in a patient with HIV infection. (17th January 2014) - Gunst, Jesper Damsgaard; Jensen-Fangel, Søren
Abstract : A 65-year-old man with HIV infection presented with acute severe abdominal pain radiating to the back. A CT scan revealed an infrarenal abdominal aortic aneurysm, and an aortobifemoral bypass was undertaken. Subsequently, tissue specimens from the aortic wall grew Listeria monocytogenes . The patient received 8 weeks of intravenous antibiotic treatment followed by oral sulfotrim as secondary prophylaxis and made an uneventful recovery.